2017
DOI: 10.1016/j.healthplace.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Association of environmental indicators with teen alcohol use and problem behavior: Teens' observations vs. objectively-measured indicators

Abstract: Most prior studies use objectively measured data (e.g., census-based indicators) to assess contextual risks. However, teens’ observations might be more important for their risk behavior. Objectives: 1) determine relationships between observed and objective indicators of contextual risks 2) determine relations of observed and objective indicators with teen alcohol use and problem behavior. Teens aged 14–16 (N=170) carried GPS-enabled smartphones for one month, with locations documented. Ecological momentary ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…For example, EMA via smartphone surveys plus geospatial technology (e.g., GPS and geographic information systems) have spawned a subtechnique called geographic EMA (GEMA; Epstein et al, ; Kirchner & Shiffman, ), which shows high spatial accuracy and little evidence that adolescent characteristics or neighborhood features are associated with inaccuracy in geographic readings (Mennis, Mason, Ambrus, Way, & Henry, ). Using GEMA, Byrnes et al () examined links between spatial context and adolescents' problem behavior among 170 youth ages 14–16 who completed EMAs on weekends for a month on GPS‐enabled smartphones. GPS‐measured density of alcohol outlets was associated with adolescents' alcohol use measured via EMA, but adolescents' EMA reports of whether they could observe an alcohol outlet at the current moment were not.…”
Section: Review Of Ema Studies Of Child and Adolescent Mental And Behmentioning
confidence: 99%
“…For example, EMA via smartphone surveys plus geospatial technology (e.g., GPS and geographic information systems) have spawned a subtechnique called geographic EMA (GEMA; Epstein et al, ; Kirchner & Shiffman, ), which shows high spatial accuracy and little evidence that adolescent characteristics or neighborhood features are associated with inaccuracy in geographic readings (Mennis, Mason, Ambrus, Way, & Henry, ). Using GEMA, Byrnes et al () examined links between spatial context and adolescents' problem behavior among 170 youth ages 14–16 who completed EMAs on weekends for a month on GPS‐enabled smartphones. GPS‐measured density of alcohol outlets was associated with adolescents' alcohol use measured via EMA, but adolescents' EMA reports of whether they could observe an alcohol outlet at the current moment were not.…”
Section: Review Of Ema Studies Of Child and Adolescent Mental And Behmentioning
confidence: 99%
“…Emerging sensor research has begun linking some dynamic measures of experience to developmental outcomes. For example, research with teenagers has found that objective GPS‐based (but not subjective) measures of physical proximity to liquor stores are associated with an increased likelihood of underage drinking (Byrnes et al, ). Such objective measures of the structure of daily experience will likely continue to reveal new insights into developmental trajectories.…”
Section: Daily Activity: a Unique Contributionmentioning
confidence: 99%
“…Subjective interpretation of stressors plays an important role in determining the individual stress response [49]) and the ways in which individuals appraise and interpret neighborhood conditions. Results from studies using both objective and subjective measures of neighborhood characteristics have been mixed with varying levels of associations with substance use or other behavioral outcomes [46, 5052]. The discordance among perceived and objective measures suggests that while they may be related, they are distinct concepts, which highlights the importance of using multiple methods to obtain a comprehensive understanding of crime and perceived safety.…”
Section: Introductionmentioning
confidence: 99%